Interrogating corporate philanthropy in education: the case of Nigeria (2019)
Upon independence from colonial rule, education held promise and hopes for the African continent. Yet, the rapid pace at which the sector grew did not sustain dreams of more schools, teachers, learners and innovations. Consequently, the twentieth century has seen schools in many countries facing conditions which have been summarised by Samoff and Carrol (2013) as having ‘no teachers’ guides, no textbooks, not even chairs’ (p.403). As of 2014, Nigeria, the largest country in Africa by population size, had over 10 million of the 57 million out-of-school children globally (UNESCO, 2014). While its out-of-school population increased by 42 per cent between 1999 and 2010, Ethiopia, the second most populous nation in Sub-Saharan Africa, had a three-quarters reduction in its out-of-school population (UNESCO, 2014).